ZAKRES KOGNICJI POLSKIEGO SĄDU ADMINISTRACYJNEGO - Piątek, Wojciech (Wydział Prawa i Administracji UAM, 2009)
The paper deals with the issue of cognition of Polish administrative courts. The doctrine formulates a number of different opinions on that matter, from a postulate to maintain the existing model which limits the court’s supervision of the legality of a public administrative act in the cassation system, to the introduction of administrative courts judicial decision as to the merits of an administration case. In the light of the existing wording of Article 184 of Poland’s Constitution, the latter proposal is currently unacceptable since its adoption would vest into the administrative court the tasks of administration, leaving organs of public administration unable to realise their goals and objectives. As a result, their activities would be taken over by courts. There are a number of other reasons supporting the current judicial supervision, including the fact that organs of public administration are highly specialised in different matters. A replacement of the cassation system of supervision with a system of appeals would also entail a necessity to revise the whole system of instance supervision, which again, would be contradictory to the currently binding Constitution. What is more, the administrative court would loose one of its immanent features namely, the power to control administration distinguish it from the jurisdiction of courts of law. This could even lead to further postulates advocating resignation from a separate judicial decision in administrative matters. Last but not least, there are historical reasons why the current model should be retained. All the arguments presented in the paper support the view that the cognition of Polish administrative courts should remain unchanged.
SCOPE OF COGNITION OF A POLISH ADMINISTRATIVE COURT